6th International Bolghar Forum - Dyrtyk-ool, Anna O. (The New Research of Tuva, 2014)
Article review the 6th International Bolghar Forum that took place on August 14-19, 2014 in the Republic of Tatarstan. It lists notable reports and presents the impressions of the conference participant.